SISTEM INFORMASI PENGGAJIAN KARYAWAN PT.LIONG EMAS ABADI PERKASA - Darson Darson; Dali Santun Naga; Ery Dewayani (Jurnal Ilmu Komputer dan Sistem Informasi, 2020)
The application program "Employee Payroll Information System of PT. Liong Emas Abadi Perkasa" aims to help the payroll system at PT. Liong Emas Abadi Perkasa from manual to computerized. This application program uses the Rapid Application Development (RAD) method which is carried out in several stages, namely the Initial Investigation, Make Prototype, the testing phase, the implementation phase and the maintenance phase. This application program uses several design tools, namely Flowcharts, Data Flow Diagrams, Entity Relationship Diagrams, Context Diagrams and Relationships Between Tables. This application program uses MySQL as a database, XAMPP as a link between the database and display, PHP as a programming language and display settings application Testing this application uses the Black box testing method and User Acceptance Test (UAT). Based on the trials conducted it can be concluded that the program created can be run and can help users in the company's payroll.